We are Designers Because We Can Abstract - Adel, A.; Djeridi, R. (Cranfield University Press, 2009)
Due to the increasing systems complexity, architecture design became an important issue. It gained interest and its importance was framed in three domains: as a way to understand complex systems, to design them, to manage their manufacturing process and to provide long-term rationality. The purpose of this paper is, firstly, to survey the existing definition approaches on architecture. Secondly, we propose a model for architecture design which articulates the potential linkage between two principle concepts: synthesis and abstraction. Our proposal model focuses on abstraction concept and permits an effective top-down design approach. It helps also designers to more respond to issues that characterize architecture design.
Organised by: Cranfield University
Keywords: System architecture; Concept; Model; Synthesis; Abstraction